2021
DOI: 10.1111/jcmm.16800
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic signature and immune efficacy of m1A‐, m5C‐ and m6A‐related regulators in cutaneous melanoma

Abstract: Cutaneous melanoma (CM) is an aggressive cancer; given that initial and specific signs are lacking, diagnosis is often late and the prognosis is poor. RNA modification has been widely studied in tumour progression. Nevertheless, little progress has been made in the signature of N1‐methyladenosine (m1A), 5‐methylcytosine (m5C), N6‐methyladenosine (m6A)‐related regulators and the tumour microenvironment (TME) cell infiltration in CM. Our study identified the characteristics of m1A‐, m5C‐ and m6A‐related regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…It is well known that the degree of immune cell infiltration is closely related to the efficacy of immunotherapy and the prognosis of cancer patients. Studies have found that immune cell infiltration was regulated by a variety of epigenetic factors, including m6a and m5c methylation ( 37 ). But as a newer type of methylation, there are few immune-related studies on m7G methylation.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the degree of immune cell infiltration is closely related to the efficacy of immunotherapy and the prognosis of cancer patients. Studies have found that immune cell infiltration was regulated by a variety of epigenetic factors, including m6a and m5c methylation ( 37 ). But as a newer type of methylation, there are few immune-related studies on m7G methylation.…”
Section: Discussionmentioning
confidence: 99%
“…28 Wu et al constructed a prediction model for SKCM, but the sample size of the validation set was too small to represent the accuracy of the model. 29 Two genes (ALOX5, CHAC1) collaborated to create a prognosis model that accurately estimated the prognosis of patients with SKCM, according to our findings. Furthermore, differences in the underlying diseases of SKCM have no impact on the expression features of the two genes, meaning that the prognosis model should be used to ALOX5 is a member of the arachidonic acid-derived family of proinflammatory lipid mediators.…”
Section: Discussionmentioning
confidence: 77%
“…Before us, most literature concerning the prognostic gene signatures of SKCM was focused on m1A-, m5C-, and m6A-methylation ( Wu et al, 2021 ); autophagy ( Deng et al, 2021 ); ferroptosis ( Xu et al, 2021 ); pyroptosis ( Ju et al, 2021 ); and oxidative stress ( Yang et al, 2021 ). For example, Yang et al built an oxidative stress–associated gene’s prognostic model for melanoma.…”
Section: Discussionmentioning
confidence: 99%